Development and evaluation of an online HIV pre-exposure prophylaxis (PrEP) training program for community pharmacists to implement pharmacy-led PrEP services in Malaysia - Yan Nee Gan; Rafdzah Zaki; Safia Alia Hafidzar; Kwee Choy Koh; Mariani Ahmad Nizaruddin; Rosnida Mohd Noh; Khairil Erwan Khalid; Andrew Yap; Frederick L. Altice; Sin How Lim; Iskandar Azwa (PLoS ONE, 2025)
Introduction Expanding HIV pre-exposure prophylaxis (PrEP) through pharmacies may improve access for key populations. As part of the preparation phase of the EPIS (Exploration-Preparation-Implementation-Sustainment) framework, we developed and evaluated an online, self-paced PrEP training program for community pharmacists to prepare for a pilot, pharmacy-led PrEP service in Malaysia. Materials and methods In May 2023, a PrEP training committee developed an online training program covering PrEP efficacy, safety, eligibility, baseline assessments, laboratory testing, prescribing, and special circumstances, and pre-/post-training knowledge tests. In June 2023, 18 community pharmacists asynchronously completed the training. Effectiveness was evaluated using a 20-question pre-/post-training knowledge test, with responses calculated into percentage scores, alongside participant feedback. Paired t-tests assessed knowledge score differences (p < 0.05). Results Participants (median age: 30.5 years [IQR: 5.8]; 78% female; 89% Chinese; median 6.5 years of experience [IQR: 4.5]; four with prior HIV-related experience) showed a mean increase in knowledge scores of 14.2% (95% CI: 8.2%–20.1%; p < 0.001), increasing from 64.7% to 78.9%. Scores for four mid-career participants (50% female, 5–10 years of experience, all with undergraduate degrees, including one with prior HIV-related training), however, did not improve, suggesting that tailored learning approaches may be needed, and that existing knowledge or prior experience do not necessarily predict learning outcomes. PrEP knowledge gaps remained primarily in counseling (−22%), identifying candidates (−12%), clinical contraindications (−6%), effectiveness (−6%), and management of missed doses for daily PrEP (−6%), highlighting potential challenges in clinical decision-making and patient communication. Most pharmacists agreed that the training was well-structured, easy to understand, of appropriate duration, and useful for their work. Satisfaction was high, as was willingness to recommend it. Conclusions The novel online self-paced training program improved pharmacists’ PrEP knowledge, though variability in knowledge gains suggests the need for enhancements. Incorporating case-based, problem-based, and simulation-based learning may improve comprehension, particularly in patient counseling, eligibility assessment, and PrEP contraindications.